Comparative Efficacy of Multiple Variables of Mesenchymal Stem Cell Transplantation for the Treatment of Neuropathic Pain in Rats. (1st March 2017) - Liu, LiPing; Hua, Zhen; Shen, Jun; Yin, Yan; Yang, Jing; Cheng, Kathleen; Liu, Aijun; Wang, Lina; Cheng, Jianguo
ABSTRACT: Objectives: The current treatment options for neuropathic pain due to nerve injuries are limited and largely unsatisfactory. Mesenchymal stem cell transplantation (MSC) has shown promise as an emerging therapy for neuropathic pain. However, a number of critical parameters, including the sources of cells, the number of cells, and routes of transplantation, need to be elucidated before it can be tested clinically. Methods: MSCs were isolated from rat bone marrow (rBM-MSCs) and adipose tissue (rAD-MSCs) and characterized by flow cytometry and functional differentiation. Rats with chronic constriction injury of the sciatic nerve were transplanted either intravenously or intrathecally with rBM-MSCs or rAD-MSCs in two different doses. The effects were evaluated by using paw withdrawal thresholds in response to noxious stimulation. The MSCs labeled with Dil dye were traced. A total of 75 Sprague–Dawley rats were used for these experiments. Results: Both intravenous and intrathecal transplantation of MSCs significantly attenuated neuropathic pain. Comparable results were achieved by either rBM-MSCs or rAD-MSCs. No differences were noted between the two doses of cell transplantation. MSCs were found on the surface of the spinal cord and dorsal root ganglia. The animals did not show any signs of toxicity throughout the whole course of the experiments. Conclusions: Both intravenous and intrathecal MSC transplantations were safe and efficacious and both rBM-MSCs and rAD-MSCs are suitable for transplantation.